Apakah Kesaksian Saksi Syarat Nikah - Maysa Putri Hairana Lubis; Nona Adelia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The status of witness testimony in Islamic marriage remains a subject of debate among scholars.This article comprehensively examines whether witness testimony is an absolute requirement or simply a supplementary element for the validity of the marriage contract. This jurisprudential analysis explores various scholarly opinions, their supporting arguments, and the practical legal implications. First, the article defines the concept of a witness in the context of Islamic marriage, drawing upon the Quran, Hadith, and prominent scholarly interpretations. The analysis includes the capacity of witnesses, the requirements they must meet, and the distinctions between witnesses in marriage contracts and other legal contexts within Islamic law. Next, the article presents the prevailing scholarly view (jumhur) which stipulates the necessity of two male witnesses for a valid marriage. Their arguments are systematically outlined, based on Quranic verses and Hadith. Conversely, the article also explores the dissenting opinion of Abu Tsaur, who argues against the absolute necessity of witness testimony. Abu Tsaur's arguments are presented objectively, considering his interpretations of relevant religious texts. The article then analyzes the root causes of this scholarly disagreement, considering differing interpretations of Quranic verses and Hadith, variations in fiqh methodology, and socio-cultural contexts. Based on this comprehensive analysis, the article examines the legal implications of the various opinions, including their impact on the validity of marriage, court proceedings, and marriage practices within society.